Role of Cadastre in Prevention from Land Grabbing in the Domain of National Lands - Mohammad Hassan Farhang (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to investigate the role of cadastre in the prevention of land grabbing in the field of national lands. Cadastre system, a system that includes comprehensive geometric data from all real estate in the country, including property characteristics, owner or owners and related rights, and provides dynamic management of the mentioned data set to the relevant authorities in the Registry of Deeds and Real Estate and Notaries can do their job with quality and speed. The method of this research is descriptive content analysis of qualitative type. In other words, the research method of this project is descriptive and non-experimental and is of correlation and consistency type. In this study, while examining the impact of cadastre on litigation and prevention of crimes in the field of land, the role of cadastral registration effects in reducing land litigation and new registration strategies in notaries and its impact on land grabbing were examined. In the property owner cadastre, the method and means of transfer of ownership of the property, geographical location and the boundaries of the four properties are determined based on the main and sub-registration numbers and the quantity and size of the property. As these cases are identified and recorded in single-page cadastral documents, as well as registered in the instant registration system, the grounds for committing registered crimes, especially land grabbing crimes, are limited, and as a result, criminal cases are reduced. Therefore, it is possible to prevent many crimes related to land grabbing by resorting to the digital cadastre plan as well as the specialized judges in the field of cadastre.